Learning optimization: Video learning media creation training using the Canva platform for kindergarten teachers - Etty Octaviani Manalu; Indrawati; Maya Pujowati; Tri Suwarningsih (University of Merdeka Malang, 2025)
The development of information and communication technology (ICT) has had a significant impact on education, including early childhood education (PAUD). In today’s digital era, technology-based learning media such as video are effective in capturing children’s attention and helping them understand material in a fun, visual, and accessible way. However, the use of technology at the PAUD level still faces challenges, particularly limited infrastructure and teachers’ low digital skills in areas such as graphic design and video editing. This community service activity aimed to improve PAUD teachers’ competence in utilizing technology through training on creating video-based learning media using the Canva platform. The main problem identified was the limited use of digital media in the learning process, largely due to a lack of training and low digital literacy among teachers. A five-day intensive training was conducted with 10 teachers from Hangtuah Hamadi Kindergarten and Kartika VI-2 Persit Entrop Kindergarten in Jayapura City. The training materials included an introduction to Canva Edu, video creation practice, presentations, and classroom implementation. Evaluation results showed the training was effective, demonstrated by active participation and the production of videos suited to early childhood characteristics. This activity fostered teacher innovation and contributed to the digital transformation of early childhood education.